Keanekaragaman Hymenoptera Parasitoid Pada Perkebunan Kelapa Sawit (Elais Guineensis Jacq.) Yang Berbatasan Dengan Hutan Sekunder - Nofri, Afrizal; Yusniwati; Yaherwandi (Jurusan Budidaya Perkebunan, 2020)
Secondary forest is primary forest that managed for forest exploitation purposes, so there are many oil palm plantations that are directly adjacent to secondary forest. Hymenopteran parasitoid is a group of the most important insect in the Hymenoptera order, because of its role as natural enemies or biological control agents against insect pests in agricultural ecosystems, including oil palm plantations. The objective of this study was to understand the diversity, species richness and abundance of Hymenopteran parasitoids in oil palm plantations which adjacent to secondary forests. The research was a survey, the purposive sampling method to determine the research location, while to determine the sample points used a systematic random sampling method. For insect collection, insect nets and yellow pan traps were used. The research was carried out in oil palm plantations located in Gunung Selasih and Siguntur Village. In each research unit there were 10 sample points with a distance of each sample point was 100 m along the transect line. The results showed that the total number of Hymenopteran parasitoids collected was 199 individuals belonging to 23 families and 94 morphospecies. Braconidae and Ichneumonidae were the Hymenopteran parasitoids family which its members were found many in the present study.